High sodium intake increases blood pressure and risk of kidney disease. From the Science of Salt: A regularly updated systematic review of salt and health outcomes (August 2016 to March 2017). Issue 12 (7th November 2018) - Malta, Daniela; Petersen, Kristina S.; Johnson, Claire; Trieu, Kathy; Rae, Sarah; Jefferson, Katherine; Santos, Joseph Alvin; Wong, Michelle M. Y.; Raj, Thout Sudhir; Webster, Jacqui; Campbell, Norm R. C.; Arcand, JoAnne
Abstract : The purpose of this review was to identify, summarize, and critically appraise studies on dietary salt and health outcomes that were published from August 2016 to March 2017. The search strategy was adapted from a previous systematic review on dietary salt and health. Studies that meet standards for methodological quality criteria and eligible health outcomes are reported in detailed critical appraisals. Overall, 47 studies were identified and are summarized in this review. Two studies assessed all‐cause or disease‐specific mortality outcomes, eight studies assessed morbidity reduction‐related outcomes, three studies assessed outcomes related to symptoms/quality of life/functional status, 25 studies assessed blood pressure (BP) outcomes and other clinically relevant surrogate outcomes, and nine studies assessed physiologic surrogate outcomes. Eight of these studies met the criteria for outcomes and methodological quality and underwent detailed critical appraisals and commentary. Five of these studies found adverse effects of salt intake on health outcomes (BP; death due to kidney disease and initiation of dialysis; total kidney volume and composite of kidney function; composite of cardiovascular disease (CVD) events including, and risk of mortality); one study reported the benefits of salt restriction in chronic BP and two studies reported neutral results (BP and risk of CKD). Overall, these articles confirm the negative effects of excessive sodium intake on health outcomes.